(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
UV-protection and near infrared camouflage are the two major camouflage protections in modern military tactics. However, not all natural and composite dyestuffs provide the above mentioned properties. In this study, green leaves were chosen as the simulating object, and the camouflage properties of cotton dyed with Lithospermum were evaluated. It was observed that the dyed cotton fabric had good UV-protection and near-infrared camouflage properties. The UV- protection effect was strongly dependent on the absorption characteristics of Lithospermum while absorbing UV radiations. The near infrared camouflage effect was mainly dependent on the reflection spectrum characteristics of Lithospermum in the near infrared waveband.